PENGARUH KOMPONEN INDEKS PEMBANGUNAN MANUSIA TERHADAP PERTUMBUHAN EKONOMI DAN TINGKAT KEMISKINAN DI INDONESIA - Nurcholifah, Irvian; Ashar, Khusnul (Journal of Development Economic and Social Studies, 2024)
Indonesia is a developing country that continues to strive for improved development, measured through economic growth. However, challenges remain, such as high poverty rates, income inequality, and the worsening impact of the COVID-19 pandemic. Human development in health, education, and living standards is considered crucial for promoting sustainable economic growth. Therefore, this study aims to analyze the influence of Human Development Index components on economic growth and poverty in Indonesia during the 2018-2022 period, using data obtained from the Central Bureau of Statistics (BPS) and applying path analysis methods. The study's results show that health and per capita expenditure have a positive and significant impact on economic growth, while education and the COVID-19 pandemic do not have a significant effect. Additionally, economic growth and education do not affect poverty; however, health and per capita expenditure have a positive and significant influence on poverty, and the COVID-19 pandemic has a negative and significant impact on poverty. Furthermore, education, health, per capita expenditure, and the COVID-19 pandemic do not significantly affect poverty through economic growth.